The Impact of Money Supply on the Performance of Financial Market Indicators - An Empirical Study on the Financial Market of the State of Egypt During the Period (2010-2021)- - chena, khadidja; cherifi, brahim (Journal of Research in Finance and Accounting, 2023)
Through this paper, we aim to know the effect of money supply on the performance of financial market indicators and to show the nature of the relationship between them. For this, simple regression models were estimated using the method of least squares based on the statistical program Eviews to test this effect after presenting the theoretical literature on the variables, the study was projected on the financial market of the State of Egypt, and a set of indicators were chosen as they reflect the price, volume and activity, which are represented in the market value, the quantity of traded shares and one of the most important indicators of the Egyptian financial market known as the EGX30 index, as for the time frame for the study, it included the period from 2010 to 2021. The study concluded that there is a direct relationship between the money supply and each of the market value, the volume of trading and the EGX30 index. The percentages ranged between 54% and 77%.